2015
DOI: 10.3389/fnint.2015.00023
|View full text |Cite
|
Sign up to set email alerts
|

The medial prefrontal cortex is crucial for the maintenance of persistent licking and the expression of incentive contrast

Abstract: We examined the role of the medial prefrontal cortex (mPFC) in reward processing and the control of consummatory behavior. Rats were trained in an operant licking procedure in which they received alternating access to solutions with relatively high and low levels of sucrose (20 and 4%, w/v). Each level of sucrose was available for fixed intervals of 30 s over 30 min test sessions. Over several days of training, rats came to lick persistently when the high level of sucrose was available and suppressed licking w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 63 publications
6
64
1
Order By: Relevance
“…For each orexigenic manipulation of the Acb, it was found that reducing neural activity in the hypothalamus (via either glutamate blockade or GABA stimulation) eliminated the Acb-mediated hyperphagia, indicating that intact hypothalamic function is necessary for the expression of Acb-driven hyperphagia. This conclusion is further bolstered by recent optogenetic studies showing that silencing the Acb shell increases consumption, stimulating that region decreases consumption, and that these effects are mediated through projections of D1-bearing Acb neurons projecting to the hypothalamus (O’Connor et al 2015; Parent et al 2015). Further work indicated that either GABA receptor or μ-OR stimulation in the Acb shell provoked expression of the immediate-early gene, Fos, in several hypothalamic regions, including the LH-PeF (Baldo et al 2004; Stratford and Kelley 1999; Zhang and Kelley 2000).…”
Section: Motivational Effects Of Telencephalic Opioids: a Cortico-strmentioning
confidence: 90%
See 2 more Smart Citations
“…For each orexigenic manipulation of the Acb, it was found that reducing neural activity in the hypothalamus (via either glutamate blockade or GABA stimulation) eliminated the Acb-mediated hyperphagia, indicating that intact hypothalamic function is necessary for the expression of Acb-driven hyperphagia. This conclusion is further bolstered by recent optogenetic studies showing that silencing the Acb shell increases consumption, stimulating that region decreases consumption, and that these effects are mediated through projections of D1-bearing Acb neurons projecting to the hypothalamus (O’Connor et al 2015; Parent et al 2015). Further work indicated that either GABA receptor or μ-OR stimulation in the Acb shell provoked expression of the immediate-early gene, Fos, in several hypothalamic regions, including the LH-PeF (Baldo et al 2004; Stratford and Kelley 1999; Zhang and Kelley 2000).…”
Section: Motivational Effects Of Telencephalic Opioids: a Cortico-strmentioning
confidence: 90%
“…The precise mechanisms underlying these effects are unclear, but a number of possibilities come to mind. For example, because electrophysiological studies have suggested that units in vmPFC encode information regarding food-associated taste characteristics (including taste hedonics) and reward valuation (Jezzini et al 2013; Parent et al 2015), the intra-PFC μ-OR-mediated increase in food intake could reflect an enhancement of the hedonic properties of the food. Nevertheless, the μ-OR stimulation-induced pattern of bout initiation coupled with the shortening of individual bouts indicates that commerce with the food does not sustain the relatively longer periods of consumption that might be expected with increased gustatory reward (Davis and Smith 1992; Ostlund et al 2013; Spector et al 1998).…”
Section: Feeding-modulatory Opioid Actions In the Pfcmentioning
confidence: 99%
See 1 more Smart Citation
“…One theory is that the dACC carries a value signal that allows decision makers to overcome a tendency to succumb to temptation (Blanchard et al 2015, Hillman & Bilkey 2010). (For related ideas, see Parent et al 2015, Passetti et al 2002, and Rushworth et al 2003.) Another complementary idea is that the dACC encodes the cost of failing to persist, thereby recruiting self-control (Blanchard & Hayden 2014, Kurzban et al 2013).…”
Section: Dacc Functionmentioning
confidence: 99%
“…Self-paced, instrumental sucrose preference task. The task design was inspired by prior studies involving ratio schedules (23), incentive contrast (24,25), and head fixation for awake, mobile mice (26). For the behavioral setup, the mouse was head-fixed but could move its body freely on a treadmill, either a skewered Styrofoam ball or a 7"-diameter plexiglass running disk, to reduce the stressful effect of restraint.…”
Section: Methodsmentioning
confidence: 99%